The little book of common sense investing : the only way to guarantee your fair share of stock market returns - Bogle, John C. (Little book big profits., 2017)
"The Little Book of Common Sense Investing is the classic guide to getting smart about the market. Legendary mutual fund pioneer John C. Bogle reveals his key to getting more out of investing: low-cost index funds. Bogle describes the simplest and most effective investment strategy for building wealth over the long term: buy and hold, at very low cost, a mutual fund that tracks a broad stock market Index such as the S & P 500. While the stock market has tumbled and then soared since the first edition of Little Book of Common Sense was published in April 2007, Bogle's investment principles have endured and served investors well. This tenth anniversary edition includes updated data and new information but maintains the same long-term perspective as in its predecessor. Bogle has also added two new chapters designed to provide further guidance to investors: one on asset allocation, the other on retirement investing"--Jacket.